2017
DOI: 10.5489/cuaj.4486
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen testing for prostate cancer screening: A national survey of Canadian primary care physicians’ opinions and practices

Abstract: Introduction: In 2014, the Canadian Task Force on Preventive Health Care (CTFPHC) recommended against routine prostate cancer screening with the prostate-specific antigen (PSA) blood test.1 We surveyed Canadian primary care physicians (PCPs) to understand their opinions and attitudes towards prostate cancer screening in 2016.Methods: Twenty PCPs piloted the survey to assess its accessibility. We distributed a flyer to 19 633 PCPs as an insert in a large mailed package inviting them to attend a national meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Modeling studies demonstrated that newly diagnosed metastatic prostate cancer cases increased by 44%-60% in the 5 years after the 2012 USPSTF recommendation ( 30 ). Similar inversions in incidence and mortality of prostate cancer were also documented by previous studies, along with steady declines of willingness in physicians and general population toward PSA screening test after the changes in the USPSTF's recommendations in Canada and Australia ( 27 , 60 ). In 2018, the USPSTF recommended discussion of the potential benefits and harms of screening with their clinician for men aged 55–69 years ( 31 ).…”
Section: Discussionsupporting
confidence: 81%
“…Modeling studies demonstrated that newly diagnosed metastatic prostate cancer cases increased by 44%-60% in the 5 years after the 2012 USPSTF recommendation ( 30 ). Similar inversions in incidence and mortality of prostate cancer were also documented by previous studies, along with steady declines of willingness in physicians and general population toward PSA screening test after the changes in the USPSTF's recommendations in Canada and Australia ( 27 , 60 ). In 2018, the USPSTF recommended discussion of the potential benefits and harms of screening with their clinician for men aged 55–69 years ( 31 ).…”
Section: Discussionsupporting
confidence: 81%
“…The observed change in global incidence of genitourinary cancers likely reflects the evolution of early detection methods, such as prostate-specific antigen (PSA) screening for prostate cancer and cross-sectional imaging for kidney cancer [ 13 , 14 ]. The widespread use of routine PSA testing led to a rapid increase in the incidence of prostate cancer in the early 1990s in the USA; however, prostate cancer incidence has been declining in recent years with the reduction in routine PSA testing [ 15 17 ]. Likewise, advances in imaging technology have led to an increase in the detection rate of kidney cancer in developed countries [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changed global incidence of genitourinary cancers indicated the evolution of early detection of disease, such as prostate-specific antigen screening for prostate cancer and cross-sectional imaging for kidney cancer [10,11]. For example, the widespread use of routine prostate-specific antigen testing led to a rapid increase in the incidence of prostate cancer in the early 1990's among USA; however, prostate cancer incidence has been declining in recent years with the reduction in routine prostate-specific antigen testing [12][13][14]. Likewise, advances in imaging technology have led to an increase in the detection rate of kidney cancer in developed countries [10].…”
Section: Discussionmentioning
confidence: 99%